The Double-Edged Swords of Autonomy and External Knowledge: Analyzing Team Effectiveness in a Multinational Organization - Haas, Martine R. (Academy of Management Journal, 2010)
Extending the differentiation-integration view of organizational design to teams, I propose that self-managing teams engaged in knowledge-intensive work can perform more effectively by combining autonomy and external knowledge to capture the benefits of each while offsetting their risks. The complementarity between having autonomy and using external knowledge is contingent, however, on characteristics of the knowledge and the task involved. To test the hypotheses, I examined the strategic and operational effectiveness of 96 teams in a large multinational organization. Findings provide support for the theoretical model and offer implications for research on team ambidexterity and multinational management as well as team effectiveness.